Arquitetura escolar e patrimônio histórico-educativo : os edifícios para a escola primária pública no Rio Grande do Sul (1907-1928) - Ermel, Tatiane de Freitas (2017)
This thesis research is inserted in the of history of education field, within the theoretical perspective of cultural history and school culture, and aims to analyze the first buildings destined for public primary schools in Rio Grande do Sul, during the First Brazilian Republic (1889-1930), relating them with the historical and educational patrimony of this state. The collection of empirical data was carried through, over all, in the Legislative Assembly of Rio Grande do Sul's Memorial and in the Map Collection of the Direction of Public Works/RS; it was carried a qualitative analysis of the reports from the Direction of Public Works/RS, Direction of Public Instruction/RS and of the pictorial files. It proposes to discuss the following question: which relations were established between the first primary school buildings, constructed by the Rio Grande do Sul Government in the first decades of the 20th century, and the historical, educational state patrimony? It carries through a cartography of the first projects, plants and photographs of the school buildings constructed by the state government, analyzing aspects of its trajectories, identifying the changes and the continuities, from a material and symbolic point of view. The temporal scope was established in accordance with the years of construction/completion of the first and the last primary school identified in this research. Therefore, the year of 1907 marks the beginning of the construction of Aula Isolada Campos da Redenção, located in the city of Porto Alegre. The date of 1928 corresponds to the completion of the elementary schools in the State, one located in the city of Passo Fundo and the other in Cruz Alta, which were constructed on the basis of the same project. During this interval (1907-1928), the study identified 18 school buildings, among reforms, adaptations and constructions carried through by the state government, which enabled a division in two great groups: adapted buildings and constructions. Of the 9 buildings that were constructed, the majority is located in the capital and/or urban zones of different cities. When analyzing the trajectory of these establishments, it was observed that great part of them follow their activities as education institutions, facing serious structural problems and a significant crisis related to its history, memory and valuation as historical and educational patrimonies. It was identified that none of these constructions is protected by the Institute of the Historic and Artistic Patrimony of the State, and it was not found any projects linked to the Secretary of Education or the Historic Patrimony sector of the Direction of Public Works with the purpose of preservation of the buildings and school collections. It was evidenced that the first buildings destined to public primary schools survive a structural, historical and memorialist crisis, as well as the indifference of the responsible agencies for its maintenance and preservation. Thus, this thesis proposes interlocution between the school architecture and the historical educational patrimony, involving the school community, the distinct institutions and public spheres and the university researchers.